Utilization of Moringa (Moringa Oleifera) as A Multi Function Plant for Conservation Land in Lumban Suhi-Suhi Village, Samosir Regency - Ginting, Nurzainah; Ginting, Nurlisa; Aulia, Dwira Nirfalini; Hidayati, Juliza (Journal of Saintech Transfer, 2018)
Toba Water Catchment Area (WCA) is approximately 369,854 ha, consists of about 65% land and 35% water. In Lake Toba WCA there is a land area of 235. 217 ha(61.23%) is classified as critical and if it is not conserved will have a major impact on WCA quality. The criticality of the land around WCA Lake Toba gives a significant impact on the aesthetic side of WCA Lake Toba.The village of Lumban Suhi-suhi located in Samosir Regency is one of the tourist destination and found quite a lot of locations with the habitat of Imperata which an indicator of critical land. Local people maintains many endemic goats namely Goat Panorusan Samosir that require good quality feed.Moringa (Moringa oleifera) is a multi-functional plant, as the Moringa (Moringa oleifera) plant has a root nodule that captures N from the air and stores it on the root so Moringa can help fertilize the soil.This dedication has been done in October 2017 in Lumban Suhi-suhi Village, Samosir and the objectives is to train the community to cultivate the Moringa plant (Moringa oleifera). The output of this dedication are the community do conservation by planting Moringa so that Lumban Suhi-suhi village and its surrounding turns green and fertile and there will be available good quality goat feed. It is also expected that Lumban Suhi-suhi village becomes a tourist village that attracts more tourists.